Tax compliance in a developing country: Understanding taxpayers’ compliance decision by their perceptions - Nkundabanyanga, Stephen Korutaro; Mvura, Philemon; Nyamuyonjo, David; Nakabuye, Julius Opiso, Zulaika (Emerald Group Publishing Ltd., 2021)
Purpose The purpose of this paper is to establish the relationship between perceived grounds for tax non-compliance or compliance behaviors and perceived tax compliance factors.